Escritura y finanzas - Iñigo Arzoz Mendizábal (Mélanges de la Casa de Velázquez)
The royal chancellery of the late middle ages was one of the central institutions of the royal administration in Navarre. In addition to serving as the royal clerk, the office acquired considerable importance in the running of court finances and the royal treasury. Thousands of chancellery orders in the documentary form of ordinances were drafted for the making of payments of all kinds and the granting of a variety of bounties, and also for the collection of and exemption from taxes and imposts. The growing number of this type of documents prompted the creation, in the early 15th century, of the position of protonotario real or chief royal clerk as the sole validating authority. These documents were thus intended for circulation among all officials responsible for handling monies, controlling finances, compiling accounts and checking the balances recorded there.